The relevance of serum carcinoembryonic antigen as an indicator of brain metastasis detection in advanced non-small cell lung cancer - Lee, Dong-Soo; Kim, Yeon-Sil; Jung, So-Lyoung; Lee, Kyo-Young; Kang, Jin-Hyoung; Park, Sarah; Kim, Young-Kyoon; Yoo, Ie-Ryung; Choi, Byung-Ock; Jang, Hong-Seok; Yoon, Sei-Chul (Tumor biology, 2012)
Although many biomarkers have emerged in non-small cell lung cancer (NSCLC), the predictive value of site-specific spread is not fully defined. We designed this study to determine if there is an association between serum biomarkers and brain metastasis in advanced NSCLC. We evaluated 227 eligible advanced NSCLC patients between May 2005 and March 2010. Patients who had been newly diagnosed with stage IV NSCLC but had not received treatment previously, and had available information on at least one of the following pretreatment serum biomarkers were enrolled: carcinoembryonic antigen (CEA), cytokeratin 19 fragments (CYFRA 21-1), cancer antigen 125 (CA 125), cancer antigen 19-9, and squamous cancer cell antigen. Whole body imaging studies and magnetic resonance imaging of the brain were reviewed, and the total number of metastatic regions was scored. Brain metastasis was detected in 66 (29.1%) patients. Although serum CEA, CYFRA 21-1, and CA 125 levels were significantly different between low total metastatic score group (score 1–3) and high total metastatic score group (score 4–7), only CEA level was significantly different between patients with brain metastasis and those without brain metastasis ( p < 0.0001). The area under the receiver operating curve of serum CEA for the prediction of brain metastasis was 0.724 ( p = 0.0001). The present study demonstrated that the pretreatment serum CEA level was significantly correlated with brain metastasis in advanced NSCLC. These findings suggested the possible role of CEA in the pathogenesis of brain invasion. More vigilant surveillance would be warranted in the high-risk group of patients with high serum CEA level and multiple synchronous metastasis.